Synthesis, structural properties, electrophilic substitution reactions and DFT computational studies of calix[3]benzofurans. Issue 56 (24th May 2016) - Islam, Md. Monarul; Akther, Thamina; Ikejiri, Yusuke; Matsumoto, Taisuke; Tanaka, Junji; Rahman, Shofiur; Georghiou, Paris E.; Hughes, David L.; Redshaw, Carl; Yamato, Takehiko
Abstract : Synthesis of highly flexible calix[3]benzofurans; effects of substituent groups on calix[3]benzofuran conformations were studied by DFT computational methods. Abstract : Calix[3]benzofurans have been synthesized by a modified TosMIC coupling reaction, followed by acid treatment and an intramolecular cyclization reaction with TMSI (trimethylsilyl iodide); X-ray analysis established the structures of two samples, both showing a cone conformation. 1 H NMR spectroscopic analyses of the calix[3]benzofurans reveal that they can adopt drastically different conformations in solution and undergo very fast conformational changes relative to the NMR time scale. Calix[3]benzofuran4a exists as two conformers, namely the cone and saddle forms, in a ratio of 83 : 17 at −50 °C. A series of calix[3]benzofuran derivatives was synthesized by electrophilic aromatic substitutions, such as bromination, formylation and acylation, to investigate the influence of the substituents on the conformations of the calix[3]benzofurans. 1 H NMR spectral analyses of the acyl derivatives at room temperature indicated that these macrocycles exist as a mixture of two isomers that are slowly interconverted on the 1 H NMR timescale. The conformational isomers of the calix[3]benzofurans and their derivatives obtained from DFT methods (based on the crystal structure analysis results) were used to estimate the total energies of the different conformations.